Specific, situated, intra-individual, ambivalent, and open: integrating and advancing the research on entrepreneurial passion - Moeller, Julia (Frontiers in Psychology, 2025)
While the research on passion for entrepreneurial activities has produced many definitions, measures, and models specifying components, predictors, and outcomes of the construct, integrating these disparate approaches with each other and with current developments in psychological science remains a challenge for the next generation of research studies. This review connects the research on entrepreneurial passion with current innovations and debates in measurement and method development, motivation, personality, and developmental psychology. The review proposes to reconsider how to measure entrepreneurial passion by (1) specifying the exact facets of entrepreneurial passion in theoretical models and measures, and (2) using psychometric and co-endorsement network models to examine the relationships among the facets and the facets’ relationships with relevant predictors and outcomes. (3) The article proposes to link passion research to ongoing debates about states, traits, and emerging stability by formulating and testing process models that distinguish between state- and trait development and include recursive feedback loops. (4) The review connects research on entrepreneurial passion to current debates in emotion and motivation research by proposing to examine the ambivalent motivation and mixed emotions accompanying entrepreneurial passion with intra-individual methods. (5) To help passion researchers build on each other’s work and enhance the trustworthiness of their work, the review calls for cumulative scientific insights by adopting multi-lab collaborations and other open science practices. (6) Finally, the review proposes a new, integrative theoretical model that distinguishes between the facets that drive affective thriving and those driving perseverance in the face of obstacles.